Sosialisasi Pembelajaran Bahasa Indonesia dengan Strategi Inovatif di SMP Negeri 1 Buay Madang - Sugiarti Sugiarti; Eni Anggraini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2020)
The learning process is a very complex concept in making a learning activity that occurs more effective, efficient and conducive. This process involves various elements in a learning environment, both teachers, students, media, and other elements that support learning interactions. Innovative Indonesian learning pays close attention to the competence and rights of students, so it is said that innovative Indonesian language learning is humanist language learning. In this connection, the goal to be achieved is that Indonesian language teachers must be able to create innovative learning models so that Indonesian language learning becomes humanist learning. Innovative learning is a student-centered learning process and believes that students have competence. Students try to make ideas about the information received, try to develop mental models by relating causal relationships, and use cognitive processes in learning. The main cognitive processes include providing attention to information relevant to selection, organizing the information in a coherent representation through the process of organizing, and combining these representations with the knowledge already in mind through the integration process.